Copula-based method for multisite monthly and daily streamflow simulation - Chen, Lu; Singh, Vijay P.; Guo, Shenglian; Zhou, Jianzhong; Zhang, Junhong (Journal of hydrology (Amsterdam), 2015)
•We proposed a method for multisite monthly and daily streamflow simulation.•The Colorado River and the upper Yangtze River were selected as case studies.•The generated data can capture the properties of the single site.•The generated data can preserve the spatial correlation at different locations. Multisite stochastic simulation of streamflow sequences is needed for water resources planning and management. In this study, a new copula-based method is proposed for generating long-term multisite monthly and daily streamflow data. A multivariate copula, which is established based on bivariate copulas and conditional probability distributions, is employed to describe temporal dependences (single site) and spatial dependences (between sites). Monthly or daily streamflows at multiple sites are then generated by sampling from the conditional copula. Three tributaries of Colorado River and the upper Yangtze River are selected to evaluate the proposed methodology. Results show that the generated data at both higher and lower time scales can capture the distribution properties of the single site and preserve the spatial correlation of streamflows at different locations. The main advantage of the method is that the trivairate copula can be established using three bivariate copulas and the model parameters can be easily estimated using the Kendall tau rank correlation coefficient, which makes it possible to generate daily streamflow data. The method provides a new tool for multisite stochastic simulation.